2005
DOI: 10.1590/s0066-782x2005001800002
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade compensada por doenças cardiovasculares no período de 1980 a 1999 - Brasil

Abstract: A decline in balanced and adjusted CVD, IHD and CBVD mortality rates was observed from 1980 to 1999 in the three States and capitals. In the State and city of RJ declines in IHD were clear as of 1990, whereas declines in CBVD occurred throughout the period studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
2
14
0
3
Order By: Relevance
“…developed regions in Brazil, in their turn, showed a reduction in mortality rate, as observed in recent study 21 . Southern and Southeastern regions were the ones to show the best results.…”
Section: Mansur Et Al Trends In the Risk Of Death From Cardiovascularsupporting
confidence: 79%
“…developed regions in Brazil, in their turn, showed a reduction in mortality rate, as observed in recent study 21 . Southern and Southeastern regions were the ones to show the best results.…”
Section: Mansur Et Al Trends In the Risk Of Death From Cardiovascularsupporting
confidence: 79%
“…Oliveira et al 27 observed a decrease in the mortality rates due to ischemic heart diseases in the populations of the same three states, in the two decades before the present study was carried out. The findings observed in our study must be ascribed to the association between ischemic heart diseases and their natural evolution to HF.…”
Section: Discussionmentioning
confidence: 56%
“…Studies conducted in Brazil have shown a trend towards a decline in DCS mortality rates, although varying, according to gender, age group, and especially regional development level. While comparing the 5 Brazilian macro regions in the period between 1980 and 1999, Mansur et al 17 and Oliveira et al 19 reported that the most developed regions also presented DCS mortality rate decline, with Southern and Southeastern Regions in a more marked fashion. The Northern Region showed a stability trend, with some age groups reporting -1980-2004 slight decline.…”
Section: Discussionmentioning
confidence: 99%
“…The major determinants for such decline cannot, therefore, be pinned down. Those hypotheses include better access to medical assistance by the population in general, scientific and technological advance in DCS diagnosis, and better understanding of the pathophysiology of these conditions [6][7][8]10,17,19 . The lack of data for the development of time series to assess DCS potential risk or protection factors, as well as of analytical epidemiologic studies to test associations between those factors and DCS mortality rates do limit more consistent explanation related to those decline in Brazil.…”
mentioning
confidence: 99%